Perceptions of Australian public relations education, 1985–1999. (September 2014) - Fitch, Kate
This article investigates perceptions of Australian public relations education during a period of significant growth. It analyses in-depth interviews with 14 practitioners and educators in conjunction with Public Relations Institute of Australia (PRIA) archives. Four themes emerged from the analysis: education, professionalisation and gender; theory and practice; developing academic legitimacy and practitioner perspectives in the curriculum. Participants understood education within a professional narrative, that is, as offering a way of establishing Australian public relations as a distinct field of expertise and confirming its professional status. The findings offer new insights into the development of Australian public relations education as it became established as a popular course of study and the role of PRIA in the constitution and transmission of public relations knowledge.